Distribution of cases encountered in oral medicine undergraduate clinic: a retrospective analysis - Ibrahim, Nurul Ruziantee; Mohd Ali, Mohd Nor Hafizi; Mohd, Farah Natashah; Khalil, Nadiah; Sahar, Nor Hanisah (IIUM Press, 2024)
Oral Medicine (OM) is a dental specialty concerning the diagnosis and non-surgical management of oral conditions closely related to medical disorders. This study aims to evaluate the distribution of OM cases at the International Islamic University Malaysia (IIUM) undergraduate dental polyclinic and to determine its relationship with sociodemographic background via disease category. Students’ OM logbooks across four academic years were used for convenient sampling. Disease categories were based on previously published studies. Total cases were classified into 22 diagnosis codes and analysed using SPSS version 23. A total of 1917 cases were recorded at the undergraduate dental polyclinic across four academic batches, from year 2010 until 2018. OM case with highest frequency was oral ulcer (31%), followed by temporomandibular disorder (23%), and pericoronitis (10%). In contrast, the least common cases were lichen planus (0.4%), oral potentially malignant disease (0.3%), and tumour (0.2%). With regards to age group, second decade age group was reported the most across the observation period. OM cases were higher in females across most disease categories and Malays were the highest ethnicity reported. The current study identified the most common OM cases encountered in IIUM undergraduate dental polyclinic. The findings may portray the disease burden in the Kuantan population in general. Knowledge of common cases is crucial to prepare clinicians with safe and competent management required in clinical practice.